Uma análise em padrões de tendência de candles para operações de compra e venda no mercado de bitcoin - SANTOS, Luis Flavio dos (2019)
The objective of this work is to analyze the patterns of high and low candles used to make orders for the purchase and sale of bitcoin on a digital platform. The choice to study the standards is that they help in decision making at the time of making the orders corresponding to what is proposed (sale or purchase), because with the standards it is possible to have a forecast of what can happen to the market. The methodology was characterized as quantitative and data analysis. A digital platform was used to carry out the purchase and sale operations of the bitcoin currency with the objective of obtaining profit with tranding, thus showing that if using the graphic analysis feature the results tend to be positive.